PENGARUH PENGELUARAN PEMERINTAH BIDANG KESEHATAN TERHADAP DERAJAT KESEHATAN MASYARAKAT KAB./KOTA DI KALIMANTAN BARAT PERIODE TAHUN 2006 2010 - B01108047, Damiri (Jurnal Curvanomic, 2013)
This study aimed to analyze the effect of government spending on health to public health districts / cities in West Kalimantan 2006-2010. Then the second objective is to classify the districts / cities in West Kalimantan government expenditure on health and health status. These results indicate that government spending health positive (significant) effect on public health because all the medical support facilities such as hospitals, health centers, and medical personnel can be met so that the health of society increases. Based on public expenditure in health and community health status compared with the average of West Kalimantan Province, the areas that come in the category of good which is the area coined government health spending is high and a high degree of health is Ketapang, Sintang, Sanggau, and Pontianak regency. While the area coined terkatagori lower health spending and a low degree is kesehatanya Hedgehogs District, and Kapuas Hulu. Keywords : Pengaruh Pengeluaran Pemerintah Bidang Kesehatan Terhadap Derajat Kesehatan Masyarakat Kab./Kota Di Kalimantan Barat Periode Tahun 2006 2010